The changing political identity of the "Overseas Chinese" in Australian Politics - Chongyi Feng (Cosmopolitan Civil Societies: An Interdisciplinary Journal, 2011)
This paper explores the role played by the Chinese communities in the Australian politics of multicultural democracy from the perspective of political socialisation and resocialisation. It argues that there is no such a thing as inherent “cultural values” or “national values” that differentiate ‘the Chinese” politically from the mainstream Australian society. This paper focuses on the Chinese nationalism of Han Chinese migrants in Australia. Within the “new mainland migrants” who have come to Australia directly from the PRC since the 1980s, nationalism is much weaker among the Tiananmen/ June 4 generation who experienced pro-democracy activism during their formative years in the 1980s. Nationalism is much stronger among the Post-Tiananmen Generation who are victims of the “patriotism campaign” in the 1990s when the Chinese Communist party-state sought to replace discredited communism with nationalism as the major ideology for legitimacy.